2014
DOI: 10.5713/ajas.2013.13395
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combining Feed Grade Urea and a Slow-release Urea Product on Characteristics of Digestion, Microbial Protein Synthesis and Digestible Energy in Steers Fed Diets with Different Starch:ADF Ratios

Abstract: As a result of the cost of grains, the replacement of grains by co-products (i.e. DDGS) in feedlot diets is a common practice. This change produces diets that contain a lower amount of starch and greater amount of fibre. Hypothetically, combining feed grade urea (U) with slow release urea (Optigen) in this type of diet should elicit a better synchrony between starch (high-rate of digestion) and fibre (low-rate of digestion) promoting a better microbial protein synthesis and ruminal digestion with increasing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…This corroborates the findings of López-Soto et al (2014), which reported an energetic advantage (increases in digestible energy) in cannulated steers when the combination of SRU + U was given at a ratio of starch and ADF identical to that used in the present experiment. In practical terms, if we consider that the diet composition of combined U treatment (SRU + U-4.5) and U treatment at the same S:ADF ratio (U-4.5, Table 1) were practically identical, the energy improvement observed for SRU + U-4.5 treatment represents the equivalent of an increase of 6.4% [(2.14 − 2.00)/2.18] of steam-flaked sorghum in the diet.…”
Section: Statistical Analysessupporting
confidence: 82%
See 4 more Smart Citations
“…This corroborates the findings of López-Soto et al (2014), which reported an energetic advantage (increases in digestible energy) in cannulated steers when the combination of SRU + U was given at a ratio of starch and ADF identical to that used in the present experiment. In practical terms, if we consider that the diet composition of combined U treatment (SRU + U-4.5) and U treatment at the same S:ADF ratio (U-4.5, Table 1) were practically identical, the energy improvement observed for SRU + U-4.5 treatment represents the equivalent of an increase of 6.4% [(2.14 − 2.00)/2.18] of steam-flaked sorghum in the diet.…”
Section: Statistical Analysessupporting
confidence: 82%
“…The treatment 1 (SRU) consisted in combining U and SRU product (Optigen II; a polymer-coated urea, Optigen, Alltech Mexico, Guadalajara, Jalisco). Accordingly to the results obtained by López-Soto et al (2014), the U combination used was at 0.80% of each one on DM basis and supplemented in a diet with 4.5 S:ADF ratio. The treatments 2, 3 and 4 were formulated by the supplementation of 0.80% of U solely in diets with 3.5, 4.5 or 5.5 S:ADF ratio.…”
Section: Animal Processing Housing and Feedingmentioning
confidence: 99%
See 3 more Smart Citations